Pengaruh Kepemimpinan, Motivasi Dan Insentif Terhadap Kinerja Karyawan CV Karya Abadi Kota Mojokerto - Syavianty, Dea; Lukito, Harjo; Ashriana, Ahfi Nova (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
CV Karya Abadi is a company engaged in the industrial sector. Companies engaged in the service sector must of course pay attention to the performance of their human resources to provide good quality. The dominant and influential factors on employee performance must always be the focus and attention. This study aims to find out and analyze how the influence of leadership variables, motivation, and incentives on employee performance in CV Karya. by using quantitative research methods. The population of this study is all employees of CV Karya Abadi Mojokerto City which is 150 people. In this study, using Sample Random Sampling is part of probability sampling. The determination of the number of samples used the Slovin formula so that a minimum sample that could be used was obtained from as many as 109 people. The results of the t-test and F-test showed that leadership, motivation, and incentives were partially and simultaneously influential shows that leadership, motivation, and incentives have a partial and simultaneous effect on performance